Cognitive Behavioral Therapy in Agoraphobia and Posttraumatic Stress Disorder: A Case Study - Ateş, Nida (My University, 2019)
Presenting Problem In the current case study, 12 sessions of Cognitive Behavioral Therapy process of a 28 years old female, who had agoraphobia and post-traumatic stress disorder symptoms according to DSM-5, was presented. The client complained of having anxiety on using any public transportation and avoided being in crowded public places and waiting in line. She also had intense anxiety when she walked alone on the street and near her neighborhood, fear of driving and being a passenger in front seat. On the other hand, these following complains started after she experienced bag snatching case in 2011 and increased symptoms once she had car accident case last year. She stated that she went to a psychiatrist one month ago and then she started taking “250 mg Selectra” per day for a month. All in all, three therapeutic goals have been set with the client. These were being able to comfortably ride in public transportation, being able to walk comfortably in the street while alone, being able to drive and being a passenger in front seat. Case Conceptualisation and Intervention It was found out that the client, who suffered from intense fear walking on the street alone and being outside near her house alone, were associated with her traumatic bag snatching experience. The client was exposed to the snatching case through the medium of imaginative exposure technique. After experiencing bag snatching as well as the impacts of intrusive and critical parenting over the client, the client’s maladaptive beliefs such as over responsibility need for control and excessive guilt were handled and changed by means of cognitive restructuring. Furthermore, the client’s another problem on “fear of driving and being a passenger in front seat” was related with her traumatic car accident that she experienced in the past. These problems based on the client's catastrophic and excessive generalized thoughts after the accident were identified and altered by cognitive restructuring. Moreover, safety and avoidance behaviors of the client were disappeared via behavioral approach. Outcome The goals that include being able to ride comfortably in public transportation, being able to walk comfortably in the street while alone and sitting in front seat of the car were achieved after the intervention. However, due to the fact that the client was out of town during the summer, the client ceased to come to therapy before the target of being able to driving has been achieved. The beliefs that the client should control the environment due to exaggerated risk perception and excessive responsibility and guilt has been discussed and changed in the context of cognitive restructuring. In addition, as a result of the treatment, the client realized that she did not experience neither catastrophic incidences as she expected in absence of safety nor experienced any avoidance behaviors. Review and Evaluation The treatment that included psycho-education about agoraphobia and post-traumatic stress disorder, cognitive restructuring, exposure, breathing and relaxation exercises was detailed in the light of the relevant literature. It is expected to contribute to CBT practice understanding of the agoraphobia based on trauma with the case study presented in this study. Presenting various CBT processes of post traumatic stress disorder cases that include different features such as chronic problems in future studies are required to enrich the relevant literature.